THE EFFECT OF THE HARZANDLER'S SIBLING MAGOMINI ON THE SUBJECT (American Journal of Interdisciplinary Research and Development, 2024)
The article highlights the important aspects of child development and, later, how few places they find in social processes and cooperate. The article also outlines the scientific research of psychologists on sibling relationships.